Analisis Bencana Banjir Menggunakan Data SAR (Synthetic Aperture Radar) Sentinel 1 di Kecamatan Sungai Serut Kota Bengkulu - Sari, Kurnia Yunita; Triyatno, Triyatno (Lembaga Yasin AlSys, 2024)
Sungai Serut Sub-district is one of the sub-districts in Bengkulu City where flooding occurs most frequently. The objectives of this study were to 1) analyze flood disasters and determine the extent of the flood area on January 06, 2022 and February 06, 2022 in Sungai Serut Subdistrict, 2) determine the number of buildings affected by flooding in 2022 in Sungai Serut Subdistrict. The method used in this research is Change Detection and Thresholding and satellite image digitization, to assess the accuracy of the data in accordance with the situation in the field, an accuracy test analysis is carried out using overall accuracy. The results showed that 1) based on the results of the analysis, the flood area on January 06, 2022 was 15.5 hectares and on February 06, 2022 was 146.32 hectares, 2) the number of buildings affected by flooding in 2022 in Sungai Serut Subdistrict was 425 buildings spread across each urban village with different numbers of buildings. Surabaya Village is the area with the highest number of buildings affected by flooding, around 343 buildings. The level of data accuracy test results obtained an accuracy percentage of 97.11% for the overall accuracy value.